Advances in 4D Printed Shape Memory Polymers: From 3D Printing, Smart Excitation, and Response to Applications. Issue 9 (16th March 2022) - Zhang, Jifeng; Yin, Zhifu; Ren, Luquan; Liu, Qingping; Ren, Lei; Yang, Xue; Zhou, Xueli
Abstract: Shape memory polymer (SMP) is a smart material that can revert from a temporary shape to a permanent shape under external stimuli, showing great potential for applications in biomedical, aerospace, and intelligent robotics fields. In recent years, with the in‐depth combination of SMP and 4D printing, many breakthroughs have been made in smart manufacturing and multifunctional integrated response. Here, the authors overview the research progress of 4D printing SMP, focusing on the diverse excitation methods, intelligent response deformation modes, and applications of 4D printing SMP. Finally, they point out the problems and future development directions of 4D printing SMP in terms of the printing process, SMP modification, structural design, and multifunctional coupling design. Abstract : This review systematically summarizes the recent progress of 4D printing based on shape memory polymers (SMPs). Some novel deformation strategies, response modes, and application directions derived from the deep combination of 4D printing and SMP are highlighted therein. Finally, the technical challenges and future research directions of 4D printing SMP are presented.